175k views
1 vote
If f(x)= 3x squares +1 and g(x) =1-x what is the value of (f-g)(2)

User Krammer
by
5.4k points

1 Answer

0 votes

Answer: (f-g)(2)=14

Explanation:

(f – g) (-2) means the same as subtracting f(2) and g(2). Since we are given f(x) and g(x), we can use them to solve. There are two ways to solve. One is to find f(2) and g(2), and then subtract them. Another way is to do (f-g)(x), then plug in x=2. I will show both methods.

Method 1

f(2)=3(2)²+1 [exponent]

f(2)=3(4)+1 [multiply]

f(2)=12+1 [add]

f(2)=13

g(2)=1-(2) [subtract]

g(2)=-1

(f-g)(2)=13-(-1) [subtract f(2) and g(2)]

(f-g)(2)=14

--------------------------------------------------------------------------------------------------------

Method 2

(f-g)(x)=3x²+1-(1-x) [distribute -1]

(f-g)(x)=3x²+1-1+x [combine like terms]

(f-g)(x)=3x²+x

(f-g)(2)=3(2)²+2 [plug in x=2, exponent]

(f-g)(2)=3(4)+2 [multiply]

(f-g)(2)=12+2 [add]

(f-g)(2)=14

--------------------------------------------------------------------------------------------------------

Now, we know that (f-g)(2)=14. We confirmed this with both methods.

User Sarath Mohan
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.